A Proteomic Study of Hemocyte Proteins from Mud Crab (Scylla paramamosain) Infected with White Spot Syndrome Virus or Vibrio alginolyticus - Sun, Baozhen; Wang, Zhi; Wang, Ziyan; Ma, Xiongchao; Zhu, Fei (Frontiers in Immunology, 2017)
In this study, we investigated the hemocytes' immune response to WSSV or V. alginolyticus infection at the protein level. The differential proteomes from crab hemocytes infected with WSSV or V. alginolyticus were analyzed using the iTRAQ (isobaric tags for relative and absolute quantitation) approach immediately after infection. Using this approach we identified 1799 proteins by their by LC-MS/MS spectra and sequencing data. These included 157 up-regulated proteins and 164 down-regulated proteins after WSSV infection. Similarly, 243 proteins were determined to be differentially expressed during V. alginolyticus infection, of these, 121 were up-regulated and 122 were down-regulated after infection. Interestingly, amongst these differentially expressed proteins, 106 were up- or down-regulated significantly in both WSSV and V. alginolyticus infection. Six genes, β-actin, myosin-9, anti-lipopolysaccharide factor isoform 4, anti-lipopolysaccharide factor 4, transketolase-like protein 2-like isoform 1, sarcoplasmic calcium-binding protein 1 were chosen for further study. The expression of these genes all showed a trend of up-regulation at 24 h post WSSV or V. alginolyticus infection except for myosin-9 in response to WSSV. To confirm the protective effects of the six genes, crabs were injected with specific dsRNAs before WSSV or V. alginolyticus challenge. The results showed that the knock down of these genes led to an increase in the morbidity and mortality (p <0.01) rate, and a decrease in infection time in WSSV-infected crabs. During the first 84 h, knock down of these genes also led to an increase in the morbidity rates in V. alginolyticus -infected crabs and results of four genes showed a higher mortality rate than that of the control after they were knocked down. This is the first report of the proteome response in crab hemocytes during WSSV or V. alginolyticus infection. These findings will contribute to our understanding of the immune response to WSSV and V. alginolyticus infection in crabs.